Integrative Approach to Dengue Hemorrhagic Fever: Clinical Management and Preventive Strategies - Tria Yune; Ovi Hawila; Pradita Dwi; Puteri Aulia; Putri Azizah; Putri Binta; Endah Kinarya Palupi (CV. FOUNDAE, 2025)
Dengue Hemorrhagic Fever (DHF) is a viral disease transmitted by Aedes aegypti mosquitoes, presenting with a wide spectrum of clinical manifestations ranging from mild fever to severe complications such as bleeding and shock. This case report describes a 12-year-old patient who presented to the Satellite Inpatient Health Center Bandar Lampung with a three-day history of high fever, headache, joint pain, skin rash, and nausea, accompanied by a positive history of mosquito bites in a dengue-endemic area. A holistic diagnostic approach was applied, including clinical history, physical examination, and symptomatic assessment. The patient was managed with fluid therapy consisting of 1500 ml oral fluids within six hours and intravenous infusion of Ringer Lactate solution (500 cc at a rate of 20 drops per minute). Preventive measures included hospitalization for observation, avoidance of mosquito bites through nets and protective clothing, fogging, and environmental sanitation. Pharmacological therapy was prescribed, including paracetamol 500 mg three times daily, ambroxol 30 mg twice daily, vitamin C 500 mg once daily, antacid 30 ml three times daily, intravenous fluids 500 cc at 20 tpm, ranitidine 150 mg twice daily, and domperidone 10 mg twice daily. Physical examination revealed a body temperature of 39°C, petechial rash, and joint tenderness, while other parameters were within normal limits. The patient reported no history of vomiting, smoking, or alcohol consumption. Following intervention, fever and pain subsided, skin rash improved, and overall clinical condition stabilized. Preventive measures were effective in reducing mosquito exposure, while supportive therapy minimized the risk of complications. This case confirms that Aedes aegypti mosquito bites caused dengue virus infection in the patient, and demonstrates that a holistic management strategy combining pharmacological therapy, fluid replacement, preventive measures, and psychosocial support can effectively reduce symptoms and prevent complications. The novelty of this report lies in its integrative approach, emphasizing early recognition and comprehensive management as essential strategies to improve patient outcomes and reduce the burden of dengue in endemic areas.